2014
DOI: 10.4187/respcare.03507
|View full text |Cite
|
Sign up to set email alerts
|

Neurally Adjusted Ventilatory Assist During Weaning From Respiratory Support in a Case of Guillain-Barré Syndrome

Abstract: We report a case of Guillain-Barré syndrome complicated by respiratory failure requiring mechanical ventilation. Neurally adjusted ventilatory assist (NAVA) allowed proper patient-ventilator synchronization by pressure support proportional to the electrical activity of the diaphragm (E di ). Prolonged ventilation with NAVA seems feasible in patients with neuromuscular impairment, but the weaning process conducted by a continuous monitoring of E di for pressure support titration needed to be assessed in a Guill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…Previous studies had shown lower tidal volumes and greater respiratory rates in NAVA compared to PSV, and such a pattern could interfere with the interpretation of an SBT. Without data on how NAVA performs during an SBT, previous studies that used NAVA during the weaning phase performed their daily SBTs either with a T-tube, PSV or CPAP [ 20 22 , 32 ]. The T-tube has been shown to yield similar results compared to minimal support in PSV during SBTs [ 33 ], but it doesn’t allow for precise FIO 2 setting nor does it provide breath-by-breath respiratory parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had shown lower tidal volumes and greater respiratory rates in NAVA compared to PSV, and such a pattern could interfere with the interpretation of an SBT. Without data on how NAVA performs during an SBT, previous studies that used NAVA during the weaning phase performed their daily SBTs either with a T-tube, PSV or CPAP [ 20 22 , 32 ]. The T-tube has been shown to yield similar results compared to minimal support in PSV during SBTs [ 33 ], but it doesn’t allow for precise FIO 2 setting nor does it provide breath-by-breath respiratory parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Dugernier khi cai thở máy cho bệnh nhân Guillain -Barré thấy hiệu suất thông khí -thần kinh của bệnh nhân khi so sánh ngày thứ nhất và ngày thứ 8 không khác biệt lúc tự thở, nhưng chỉ số này đo khi thở NAVA có giảm có ý nghĩa; p < 0,001. Từ đó, tác giả cho rằng nên theo dõi chỉ số Vt/Edi khi cai thở máy 7 . Tìm mức NAVA hợp lý khi bắt đầu tiến hành cai thở máy phương thức NAVA có vai trò quan trọng để cơ hô hấp bệnh nhân hoạt động ở mức độ thích hợp nhất, mức NAVA thấp đòi hỏi cơ hô hấp phải hoạt động nhiều, ngược lại, mức NAVA cao sẽ không cần thiết.…”
Section: Bàn Luậnunclassified